1971
DOI: 10.1107/s0021889871007027
|View full text |Cite
|
Sign up to set email alerts
|

The development of the rolling texture in copper measured by neutron diffraction

Abstract: Three-dimensional orientation distribution functions of the crystallites in copper sheets, cold rolled to different degrees of reduction, have been determined using neutron diffraction pole figures. The main features of the textures may be represented by the orientation 'tube' already described in prior publications. Two ranges of rolling reduction can be distinguished, a lower one (30 to 50 %) and a higher one (70 to 95 %) the texture changes of which correspond to those calculated after the Taylor theory. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
1
1

Year Published

1971
1971
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 1 publication
2
6
1
1
Order By: Relevance
“…It can be concluded that after 31% deformation the {112}<111> (or {4 4 11}<11 11 8>) texture component is already considerably stronger than the {110}<112> component. This is in contradiction with the observations presented by Bunge et al (13) and by Kallend and Davies (14), who observed a stronger {110}<112> component up to 70% and 95% rolling deformation, respectively. The orientations measured with the T.E.M.…”
Section: Introductioncontrasting
confidence: 57%
“…It can be concluded that after 31% deformation the {112}<111> (or {4 4 11}<11 11 8>) texture component is already considerably stronger than the {110}<112> component. This is in contradiction with the observations presented by Bunge et al (13) and by Kallend and Davies (14), who observed a stronger {110}<112> component up to 70% and 95% rolling deformation, respectively. The orientations measured with the T.E.M.…”
Section: Introductioncontrasting
confidence: 57%
“…8 for the rolling texture of 86% cold rolled iron (SchlS.fer & Bunge, 1974). In this case and others (Bunge & Haessner, 1968;Bunge, Tobisch & Sonntag, 1971;Bunge, Schleusener & SchlS.fer, 1974) the estimation gives a probable contribution of the odd terms of about 40% compared with the even terms. That is, the odd terms may constitute about 30% of the whole distribution function.…”
supporting
confidence: 59%
“…Thus the rolling texture of copper was found to consist of a tube of preferred oreintations running from {110} (112) to a high index oreientation between {112} (111) and {4 4 11} (11 11 8) 6 The orientation density measured along the central line of this tube increased from about 12 times the random density at the {110} (ll2)-end to about 15 at the other end for the 95 cold rolled texture. During rolling the severity of this texture component did not develop continuously, rather it passed through a minimum at 70o reduction.…”
mentioning
confidence: 99%